Mitochondria in reproduction and fertility: mitochondria and embryo 2 - Panloup, Pascale May (Henry Stewart Talks, 2018)
Mitochondria and embryogenesis, Mitochondria and ovarian ageing, The role of cumulus granulosa cells, Mitochondrial genetics and fertility, Targeting mitochondria to improve oocyte quality